C1QA and C1QC modify age‐at‐onset in familial amyloid polyneuropathy patients. Issue 4 (7th March 2019) - Dias, Andreia; Santos, Diana; Coelho, Teresa; Alves‐Ferreira, Miguel; Sequeiros, Jorge; Alonso, Isabel; Sousa, Alda; Lemos, Carolina
Abstract: Objectives: Transthyretin (TTR) familial amyloid polyneuropathy (FAP) (OMIM 176300) shows a variable age‐at‐onset (AO), including within families. We hypothesized that variants in C1QA and C1QC genes, might also act as genetic modifiers of AO in TTR‐FAP Val30Met Portuguese patients. Methods: We analyzed DNA samples of 267 patients (117 families). To search for variants, all exons and flanking regions were genotyped by automated sequencing. We used generalized estimating equations (GEEs) to take into account the non‐independency of AO among relatives. Intensive in silico analyses were performed, using various software to assess miRNAs target sites, splicing sites, transcription factor binding sites alterations, and gene–gene interactions. Results: Two variants for C1QA gene, GA genotype of rs201693493 ( P  < 0.001) and CT genotype of rs149050968 ( P  < 0.001), were significantly associated with later AO. In silico analysis demonstrated, that rs201693493 may alter splicing activity. Regarding C1QC, we found three statistically significant results: GA genotype of rs2935537 ( P  = 0.003), GA genotype of rs201241346 ( P  < 0.001) and GA genotype of rs200952686 ( P  < 0.001). The first two were associated with earlier AO, whereas the third was associated with later‐onset. Interpretation: C1QA was associated with later onset, whereas C1QC may have a double role: variants may confer earlier or later AO. As found in a study in Cyprus, we confirmed the role of complement C1Q genes (and thus of inflammation) as modulator of AO in Portuguese patients with TTR‐FAP Val30Met.